Income Diversification, Inequality and Poverty among Rural Households in Oyo State, Nigeria - Alawode, Olubunmi O; Oluwatayo, Isaac B; Abdullahi, Afusat O (Journal of Economics and Behavioral Studies, 2017)
The study examined income diversification, inequality and poverty among rural households in Oyo state, Nigeria. Cross-section data were generated from the survey conducted on a sample of 200 households with the aid of structured questionnaire using multi-stage sampling procedure. Descriptive statistics, diversification index, Gini coefficient, FGT poverty index, and the Probit regression model were used to analyze data. Mean income diversification index of 1.22 shows that majority of the respondents had multiple streams of income but crop farming had the largest share (90%) in total income. Mean income of respondents was ₦77,613.2±83575.01, and Gini coefficient of 0.48, 0.46, and 0.39 were obtained for total income, nonagricultural income, and agricultural income respectively. The poverty line was ₦6,490.50 and mean per capita expenditure was ₦9,735.74. The head count ratio showed that 53.5% of the households were poor while 46.5% were regarded as non-poor, and poverty gap was 0.214. From probit results, age, secondary occupation, and farm size had significant inverse relationship with poverty status. Having primary and secondary income sources is poverty reducing, therefore, rural households should be encouraged to remain in farming, especially crop farming, and motivated through skill acquisition to diversify into other income generating activities.